2006
DOI: 10.1117/2.1200610.0430
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent video display can improve visual detail and quality on mobile devices

Abstract: An algorithm-based scheme can improve video sequences originally captured for viewing on standard-size TV or HDTV that are difficult to watch on small-panel LCDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Along with the two factors, perceived mobility and viewing experience were included in this research, because they are found to be critical for mobile devices such as the iPad or iPhone (Kim, 2006;Kim et al, 2006;Park and Kim, 2011). Perceived mobility is defined as a user's personal feeling about a specific device's portability.…”
Section: Technology Acceptancementioning
confidence: 99%
“…Along with the two factors, perceived mobility and viewing experience were included in this research, because they are found to be critical for mobile devices such as the iPad or iPhone (Kim, 2006;Kim et al, 2006;Park and Kim, 2011). Perceived mobility is defined as a user's personal feeling about a specific device's portability.…”
Section: Technology Acceptancementioning
confidence: 99%
“…This new technique is a variant of the filtering technique proposed in [91]. Numerous filtering techniques used also morphological operators, wavelets or partial differential equations [92,93].…”
Section: Color Image Filtering and Enhancementmentioning
confidence: 99%